Children with psoriasis and COVID‐19: factors associated with an unfavourable COVID‐19 course, and the impact of infection on disease progression (Chi‐PsoCov registry). (6th July 2022) - Zitouni, J.; Bursztejn, A.‐C.; Belloni Fortina, A.; Beauchet, A.; Di Lernia, V.; Lesiak, A.; Thomas, J.; Topkarci, Z.; Murashkin, N.; Brzezinski, P.; Torres, T.; Chiriac, A.; et al.
Abstract: Background: The COVID‐19 pandemic has raised questions regarding the management of chronic skin diseases, especially in patients on systemic treatments. Data concerning the use of biologics in adults with psoriasis are reassuring, but data specific to children are missing. Moreover, COVID‐19 could impact the course of psoriasis in children. Objectives: The aim of this study was therefore to assess the impact of COVID‐19 on the psoriasis of children, and the severity of the infection in relation to systemic treatments. Methods: We set up an international registry of paediatric psoriasis patients. Children were included if they were under 18 years of age, had a history of psoriasis, or developed it within 1 month of COVID‐19 and had COVID‐19 with or without symptoms. Results: One hundred and twenty episodes of COVID‐19 in 117 children (mean age: 12.4 years) were reported. The main clinical form of psoriasis was plaque type (69.4%). Most children were without systemic treatment (54.2%); 33 (28.3%) were on biologic therapies, and 24 (20%) on non‐biologic systemic drugs. COVID‐19 was confirmed in 106 children (88.3%) and 3 children had two COVID‐19 infections each. COVID‐19 was symptomatic for 75 children (62.5%) with a mean duration of 6.5 days, significantly longer for children on non‐biologic systemic treatments ( P  = 0.02) and without systemic treatment ( P  = 0.006) when compared with children on biologics. The six children who required hospitalization were more frequently under non‐biologic systemic treatment when compared with the other children ( P  = 0.01), and particularly under methotrexate ( P  = 0.03). After COVID‐19, the psoriasis worsened in 17 cases (15.2%). Nine children (8%) developed a psoriasis in the month following COVID‐19, mainly a guttate form ( P  = 0.01). Discussion: Biologics appear to be safe with no increased risk of severe form of COVID‐19 in children with psoriasis. COVID‐19 was responsible for the development of psoriasis or the worsening of a known psoriasis for some children.